Novas espécies de Nothobrya Arlé, 1961 (Collembola, Entomobryidae) - França, Josemária Silva de (2019)
Collembola holds small arthropods, commonly found on soil, living in humid environments rich in organic matter. Entomobryidae gathers the most diversified and numerous forms of the group, and its current systematics includes seven subfamilies. Nothobrya Arlé is inserted in the subfamily Nothobryinae, being characterized by the presence of post- antennal organ; absence of body scales; 8 + 8 eyes; antennae with six segments (first and second segments subdivided); and trochanteral organ with 4–15 chaetae. The genus is currently represented by two described species: N. schubarti Arlé and N. arlei Silveira & Mendonça, recorded from Piauí, Pernambuco and Rio de Janeiro States. The two descriptions of N. schubarti are poorly detailed, lacking information about dorsal head and body chaetotaxy, while N. arlei has some omissions in the dorsal chaetotaxy description and nomenclature of the chaetae, as well as in the morphology of labial triangle and dorsal manubrium. This study consists in the description of two new species of Nothobrya, presenting new morphological information to the genus previously unknown. The collections were made in two municipalities: Jardim do Seridó, Rio Grande do Norte and Porto Velho, Rondônia, using pitfall traps and entomological aspirators. The specimens were analyzed and described using specific literature. Nothobrya sp. nov. 1 and Nothobrya sp. nov. 2 differs from known species of the genus in the number of dorsal chaetae and resembles these species by the colour pattern and habitus. However, Nothobrya sp. nov. 1 differs from Nothobrya sp. nov. 2 by the number of spine-like chaetae in the trochanteral organ, chaetae in the tenaculum, morphology tenent hair shape. Nothobrya sp. nov. 1 and Nothobrya sp. nov. 2 also differs from Nothobrya arlei by number of dorsal chaetae and the body sensillae formula plus anterior and posterior collophore chaetotaxy. This study contributed with the description of two new species to the genus Nothobrya, adding detailed morphological information to the taxon. Additionally, the record and description of new species allows the planning and efforts related to future actions in the environmental conservation field.